PENGARUH KONSENTRASI NAA DAN BAP TERHADAP PERTUMBUHAN TUNAS EKSPLAN TANAMAN PISANG CAVENDISH (Musa paradisiaca L.) MELALUI KULTUR IN VITRO - Saktiyono Sigit Tri Pamungkas (Gontor AGROTECH Science Journal, 2015)
The objectives of this research were to find the optimized combination micropropagation technique of Pisang “Cavendish” using Napthaleneacetic acid (NAA) and Benzylaminopurin (BAP) on culture in vitro. The research was conducted in Balai Benih Induk Hortikultura laboratorium (270 m upper sea level) Salaman, Magelang, Central Java from November 2008 - Januari 2009. Design used was Complete Randomized Design. Experimental factor were concentration of NAA and BAP. NAA concentration comparised four levels (0, 1, 2, and 3 ppm). BAP concentration comparised four levels (0, 3, 6, and 9 ppm). Obtained data was analyzed by F test, when significantly different then followed by LSD test with 5% level. Observed variables is longest roots, total of buds, and total of roots. Statistic analysis result showed that concentration of BAP have significant effect on longest roots. Concentration 0 ppm of BAP (B0) yielding optimalized on longest root ( 8,3 cm). Concentration of NAA have significant effect on longest roots. Concentration 2 ppm of NAA (N2) yielding optimalized on longest root (6,0 cm). Concentration of BAP have significant effect on total buds. Concentration 9 ppm of BAP (B3) yielding optimalized on total of buds (2,5).